The Apostolic Fathers - Foster, Paul (Ancient literature for New Testament studies, 2025)
"Ancient Literature for New Testament Studies is a multivolume series that seeks to introduce key ancient texts that form the cultural, historical, and literary context for the study of the New Testament"-- Provided by publisher